Ultrathin Nanoflakes Assembled 3D Hierarchical Mesoporous Co3O4 Nanoparticles for High‐Rate Pseudocapacitors. (2nd June 2014) - Fan, Yuqian; Shao, Guangjie; Ma, Zhipeng; Wang, Guiling; Shao, Haibo; Yan, Shuai
<x xml:space="preserve">Abstract</x> A novel 3D hierarchical mesoporous Co3O4 structure assembled by ultrathin nanoflakes (2.4 nm in thickness) has been successfully developed. Combining a high specific surface area (183.8 m2 g–1), mesoporosity, and a stable 3D hierarchical structure render the as‐synthesized 3D Co3O4 the properties of a promising active material for high‐rate pseudocapacitors with high specific capacitance, excellent rate capability, and durable long‐term stability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>